Client/server connection establishing and configuration / Loo Chee Keong - Loo , Chee Keong (2002)
This report will firstly cover the introductory or the client/server architecture. In this part, I will try to give a lull definition of the client/server architecture. Secondly, this report will review the literature. In this part, I started with the basic knowledge about the client/server technologies. At the end, I have discussed about the analysis on some other existing system models such as the Centralized Multi-User Architecture and Distributed-User Architecture. The first chapter of the methodology part is describing the methods that are suggested and have been used to define client/server architecture and to develop a client/server system model. The next chapter in this part covers the system and application design, module design and interface design. Finally, in implementation part I will show the ways to establish a client/server connection to Oracle Database Server with windows 2000. Also stated will be the implementation and testing for this application called the “FSKTM Multimedia Database”. Finally, a brief and attractive user manual will be stated in the last chapter.